LAPARASCOPIC VERSUS OPEN MESH REPAIR FOR RECURRENT INGUINAL HERNIA: A SYSTEMATIC REVIEW - Gabriel, Kevin; Junior Berhimpon, Siemon (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Inguinal hernia is one of the most common conditions seen in clinic, and is often treated through the general surgery department. Laparoscopic repair and open repair with mesh are the typical treatments for inguinal hernia, and both regimens have proved beneficial in treating inguinal hernia. However, recurrence, with a rate as high as 33, poses a significant problem to the effective treatment of inguinal hernia.The aim: This study aims to show about laparascopic versus open mesh repair for recurrent inguinal hernia. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 10 articles, whereas the results of our search on SagePub brought up 60 articles. The results of the search conducted for the last year of 2013 yielded a total 2 articles for PubMed and 14 articles for SagePub. The result from title screening, a total 1 articles for PubMed and 10 articles for SagePub. In the end, we compiled a total of 7 papers. We included five research that met the criteria. Conclusion: The laparoscopic approach is superior to the open mesh approach for the repair of recurrent inguinal hernia in some aspects, including the incision infection rate and length of hospital stay. However, more high-quality studies on the effects of laparoscopic and open mesh repair for the treatment of recurrent inguinal hernia are warranted.